ANALYSIS OF PEDAGOGICAL APPROACHES IN OVERCOMING DIFFICULTIES IN READING ARABIC FOR STUDENTS AT MADRASAH IBTIDAIYYAH NURUL YAQIN SUNGAI DUREN - Riski, Ahmad; Sahrizal Pahlepi; Agung Yusup; Neldi Haryanto; Ady Muh. Zainul Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the pedagogical approaches applied by teachers in overcoming students' difficulties in reading Arabic (maharah qira'ah) at Madrasah Ibtidaiyyah Nurul Yaqin Sungai Duren. The ability to read Arabic is an essential foundational skill that students need to master; however, in practice, various difficulties are still found that hinder the learning process. This research employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The data sources included Arabic language teachers and students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, using source triangulation and member checks to ensure data validity. The findings indicate that the pedagogical approach implemented by the teacher is student-centered learning, employing methods such as shared reading,轮流 reading (reading in turns), repeated practice, discussion, and individual guidance. The teacher also applies scaffolding strategies by providing gradual assistance to students experiencing difficulties. The reading difficulties encountered by students include: first, difficulty distinguishing Hijaiyah letters that have similar shapes, such as ب (ba), ت (ta), and ث (tsa), as well as ج (jim), ح (ha), and خ (kha). Second, errors in reading vowel marks (harakat). Third, difficulty pronouncing new vocabulary. The factors causing these difficulties consist of internal factors (differences in basic abilities, low mastery of letters) and external factors (lack of practice at home, limited learning time). The pedagogical approaches applied proved effective in overcoming students' reading difficulties. This is evidenced by improvements in students' ability to recognize letters, accuracy of pronunciation, reading fluency, as well as increased motivation and self-confidence. This study recommends that teachers continue to develop varied and adaptive pedagogical approaches, and enrich learning media to support the improvement of students' Arabic reading skills.